1997
DOI: 10.1002/(sici)1097-0215(19970304)70:5<524::aid-ijc6>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of latent and replicative Epstein‐Barr‐virus genes in bone‐marrow and peripheral‐blood mononuclear cells of healthy donors

Abstract: Reverse-transcriptase polymerase chain reaction has been used to analyze the expression of 2 latent genes (EBNA-1 and LMP-1) and one replicative gene (BZLF-1) of Epstein-Barr virus in mononuclear cells from bone marrow and peripheral blood of healthy donors. EBV-gene transcription was detected in 8 out of 15 bone-marrow samples. Among these, 5 allowed the detection of latency-associated transcripts in the absence of BZLF-1 expression. Only one sample showed positivity for expression of both latent and lytic ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Data generated by Khan et al (36) demonstrated that EBV viral DNA loads are stable in individuals over time periods spanning several years. Periodic reactivations of the EBV virus in the peripheral blood have also been demonstrated, suggesting that the stability DNA load over time is not that way because the virus is quiescent (32,33). Our data demonstrating that CD8 ϩ T cell frequencies to two different EBV epitopes are also stable over time suggest that during persistent viral infections a long term homeostasis exists between the virus and the immune system.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Data generated by Khan et al (36) demonstrated that EBV viral DNA loads are stable in individuals over time periods spanning several years. Periodic reactivations of the EBV virus in the peripheral blood have also been demonstrated, suggesting that the stability DNA load over time is not that way because the virus is quiescent (32,33). Our data demonstrating that CD8 ϩ T cell frequencies to two different EBV epitopes are also stable over time suggest that during persistent viral infections a long term homeostasis exists between the virus and the immune system.…”
Section: Discussionmentioning
confidence: 55%
“…Although it has been suggested that the differential response of CD8 ϩ T cells to lytic and latent Ags is due to different stages of the EBV lifecycle (13), all of the latent gene products are expressed during the lytic cycle (31). Lytic proteins also appear to be expressed periodically during latent EBV infection (32,33). Recently, it has been reported that although the EBNA-3A protein is expressed by cultured BLCL lines in vitro, EBNA-3A expression was not detected in either the peripheral blood or tonsillar cells of latently infected healthy, EBV-seropositive donors (34).…”
Section: Discussionmentioning
confidence: 99%
“…Viral gene expression studies were previously performed to assess the state of infected lymphocytes in the blood, and the majority of studies concluded that lymphocytes in the blood are strictly latent. However, some studies detected the expression of the lytic transactivator, BZLF1, and concluded that lymphocytes in the blood may also undergo a permissive infection during infectious mononucleosis [28][29][30][31][32]. The findings that 71% of the plasma samples analyzed in the present study contained at least 1 unique strain that was not detected in the lymphocytes and that 31% of plasma samples contained a completely discordant strain profile, compared with that in PBLs, suggest that infected circulating lymphocytes may not be the source of this virus.…”
Section: Discussionmentioning
confidence: 70%
“…This finding contrasts with those from other studies that found few or absent responses to latent antigen-derived epitopes during AIM and decreased responses to lytic antigen-derived epitopes during persistent EBV infection [9,10,17], and this difference in findings may be because the present study was based on a larger number of tested epitopes and a more genetically heterogeneous population. The detection of responses to latent antigen-derived epitopes during AIM and responses to lytic antigen-derived epitopes during persistent EBV infection suggests that sporadic, asymptomatic EBV reactivation may support long-term maintenance of responses to lytic antigen-derived epitopes during persistent EBV infection [42,43] and that the presence of latently infected cells with a type III gene expression profile (EBNA-3 and latent membrane proteins 1 and 2) during AIM may induce early responses to latent antigen-derived epitopes [44,45]. In addition, sporadic exposure to infectious virus may further contribute to the maintenance of responses to lytic antigen-derived epitopes during persistent EBV infection.…”
Section: Discussionmentioning
confidence: 99%